Implementasi Program Pengembangan Kreativitas Guru dan Anak Usia Dini Melalui Kegiatan Gebyar HIMA PGPAUD Universitas Islam Al-Ihya Kuningan - Iskandar, Yogi; Nuryati, Nunung; Darmayanti, Darmayanti; Destiyanti, Ika Candra; Iman, Iman; Setiana , Setiana (Journal of Community Research & Engagement, 2025)
The "Gebyar HIMA PGPAUD UNISA 2023" event is a community service program aimed at enhancing the creativity and knowledge of Early Childhood Education (PAUD) teachers and stimulating the development of early childhood through various educational activities. The program includes seminars, workshops, and creativity competitions involving teachers and PAUD children in the III Cirebon region. This activity is also designed to support the implementation of the Merdeka Curriculum with a project-based and neuroscience approach. The results of this event show high enthusiasm from participants, both teachers and children, who actively participated in various activities. This program is expected to contribute positively to improving the quality of early childhood education in the region and strengthen the role of Universitas Islam Al-Ihya (UNISA) Kuningan in advancing education through community service initiatives